Performance enhancements of DFIG wind turbine using fuzzy-feedback linearization controller augmented by high-gain observer - Kada Boureguig; Abdellah Mansouri; Ahmed Chouya (Institute of Advanced Engineering and Science, 2020)
This paper proposes a feedback linearization control of doubly fed induction generator based wind energy systems for improving decoupled control of the active and reactive powers stator. In order to enhance dynamic performance of the controller studied, the adopted control is reinforced by a fuzzy logic controller. This approach is designed without any model of rotor flux estimation. The difficulty of measuring of rotor flux is overcome by using high gain observer. The stability of the nonlinear observer is proved by the Lyapunov theory. Numerical simulations using MATLAB-SIMULINK shown clearly the robustness of the proposed control, particularly to the disturbance rejection and parametric variations compared with the conventional method.